Evaluation of a Macro Lump Plasticity Model for Reinforced Concrete Beam-Column Joint under Cyclic Loading - Joko Purnomo; V. Octaviani; P. K. Chiaulina; Jimmy Chandra (Civil Engineering Dimension, 2020)
Lateral deformations of reinforced concrete (RC) frames under extreme seismic excitation are highly affected by the stiffness of their beam-column joints. Numerous models have been proposed to simulate the responses of RC beam-column joint under cyclic loading. Development of RC beam-column joint model based on macro modeling using spring elements becomes more popular because of its considerably simple application for seismic performance evaluation purposes. In this study, a simple modification to previously developed macro-spring element-based model for RC beam-column joint is done and is used to simulate the behavior of seven external and five internal RC joints under cyclic loading in SAP2000. The model consists of several spring elements to define column, beam, joint, and bond-slip responses according to its individual moment-rotation relationships. Overall, the analysis results show that the modified model can simulate well the cyclic behavior of RC beam-column joints when are compared to previously available experimental results